Perubahan Perilaku Sosial Penggunaan Smartphone Peserta Didik - Indryani Febriyanti Ade, Maria; Chotimah, Nur; H. ABD. Rahman, Nurdin (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2021)
The world is eyeing the development of smartphones where their use is not only used as a medium of communication but as a medium of entertainment and education. This study aims to determine changes in the social behavior of students' smartphone use in one of the high schools in the East Nusa Tenggara SikkaDistrict. This study uses a qualitative approach to measuring research data collection tools using observation, interviews, and documentation. Based on the results of the study found that changes in social behavior can be seen from the interaction and socialization in the school environment both during school breaks and when teaching and learning activities take place. Behavior change is found, character shifts have an impact on the school environment's lack of oral communication, and more choose to enjoy their smartphone than reading books in the library. The measuring rod of smartphone usage by students is their independence in doing school work, which can be accessed via the internet and electronic books as supporting media in the learning process